Base of the Column of Antoninus Pius
Front: the Apotheosis (deification) of Emperor Antoninus Pius (138-161 AD) and his wife Faustina, carried by a winged youth (Aion, eternal time). On the sides: simulation of a cavalry battle during the emperor's funeral.